'I felt less alone knowing I could contribute to the forum': psychological distress and use of an online infertility peer support forum. Issue 1 (1st January 2021) - O'Connell, Siobhan Bernadette Laura; Gelgoot, Eden Noah; Grunberg, Paul Henry; Schinazi, Joy; Da Costa, Deborah; Dennis, Cindy-Lee; Rosberger, Zeev; Zelkowitz, Phyllis
ABSTRACT: Background: Feelings of loss, shame and stigmatization, reduced quality of life, isolation and loneliness are common among men and women with infertility. Fertility patients may seek peer mentoring and support, specifically through the use of online forums, to fulfil their needs for shared experience and guidance through the fertility treatment process. Objective: To assess the use and benefits of an online fertility-related peer support forum through two research questions: (1) do socio-demographics, stress, and anxiety differ between posters on the forum, lurkers who read messages but did not post, and people who chose not to use it?; and (2) how did forum users describe their experiences? Design: A sample of 220 male and female fertility patients aged 23–54 years old (M = 35.51, SD = 4.94) were recruited at fertility clinics in Montreal and Toronto, Canada, to test a mobile application called ' Infotility '. They answered questionnaires before and after being given access to Infotility for eight weeks. The peer support forum was accessible through the Infotility dashboard. Main Outcome Measures: Psychological distress was measured through the 4-item Perceived Stress Scale and the Generalized Anxiety Disorder 7-item Scale. Experiences using the forum were assessed through open-ended questions and in-depth interviews. Results: Participants with heightened psychological distress were more likely to become posters rather than lurkers or non-users and reported less distress after using the forum. Forum users appreciated the opportunity to share their experiences with others in similar situations. Conclusion: The forum reduced loneliness and allowed participants to learn new ways to manage stress. It was particularly beneficial for those with heightened psychological distress.